Model Pembelajaran Inkuiri dan Discovery Learning dalam Administrasi Pendidikan - Khoirunisa; Adelia Yuliani; Siti Alfiah; Eva Iryani (FKIP Universitas Palangka Raya, 2026)
The shift in the educational paradigm toward a student-centered approach demands innovation in instructional strategies, including in educational administration. This article examines two innovative learning models—Inquiry and Discovery Learning—and their relevance for application in the context of educational administration. Grounded in constructivist theory, both models focus on developing critical, analytical, creative, and problem-solving skills that are essential for prospective educational administrators. Through a literature review, this article outlines the principles, characteristics, as well as the strengths and limitations of each model. In addition, examples of their application in learning are presented, such as analyzing cases of school conflict and designing data-based budgeting. The article also discusses supporting and inhibiting factors in implementation, emphasizing the strategic role of administrators in creating a collaborative and adaptive learning environment. It is concluded that the implementation of Inquiry and Discovery Learning models contributes to improving the quality of educational administration and prepares graduates who are competent, reflective, and responsive to the challenges of 21st-century education.